2020
DOI: 10.1101/2020.10.22.20217521
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of Mycobacterium tuberculosis-specific Th22 cells and the effect of tuberculosis disease and HIV co-infection

Abstract: The development of a highly effective tuberculosis (TB) vaccine is likely dependent on our understanding of what constitutes a protective immune response to TB. Accumulating evidence suggests that CD4+ T cells producing IL-22, a distinct subset termed Th22 cells, may contribute to protective immunity to TB. Thus, we characterized Mycobacterium tuberculosis (Mtb)-specific Th22 (and Th1 and Th17) cells in 72 individuals with latent tuberculosis infection (LTBI) or TB disease, with and without human immunodeficie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(140 reference statements)
0
1
0
Order By: Relevance
“…The elevated levels of IL-22 were also found in the pleural fluid and blood of tuberculosis patients, although IL-22 can be either beneficial or harmful to tuberculosis progression depending upon the host situation [34,35]. Makatsa and his colleagues reported that M. tuberculosis-specific IL-22 was exclusively produced by the CD4 + T cells of healthy donors with latent tuberculosis infection [46]. Moreover, the subcutaneous injection of CFA increased the level of IL-22 in the blood and activated mycobacterial antigen-specific effect T cells in the spleen [47].…”
Section: Discussionmentioning
confidence: 99%
“…The elevated levels of IL-22 were also found in the pleural fluid and blood of tuberculosis patients, although IL-22 can be either beneficial or harmful to tuberculosis progression depending upon the host situation [34,35]. Makatsa and his colleagues reported that M. tuberculosis-specific IL-22 was exclusively produced by the CD4 + T cells of healthy donors with latent tuberculosis infection [46]. Moreover, the subcutaneous injection of CFA increased the level of IL-22 in the blood and activated mycobacterial antigen-specific effect T cells in the spleen [47].…”
Section: Discussionmentioning
confidence: 99%